PENERAPAN BUDIDAYA PADI ORGANIK UNTUK MENGHASILKAN PANGAN YANG SEHAT DAN KEBERLANJUTAN USAHA TANI - Toana, Moh. Hibban; Mile, Yuldi; Pasaru, Flora; Khasanah, Nur; Haji Nasir, Burhanuddin (Universitas Mataram, 2024)
Organic rice cultivation is a way of growing rice without using inorganic fertilizers and synthetic chemical pesticides. The fertilizer used is organic fertilizer and pest and disease control is carried out using the concept of integrated pest control. The